Improving Simple Past Tense Mastery Used in Recount Text Through the Use of English Songs at the Eleventh Grade Students of SMA Negeri 2 Sigi - Nindi Putri Asylva; Jamiluddin, Jamiluddin; Maf'ulah, Maf'ulah; Manurung, Konder (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The objective of this research is to prove that the use of English songs can improve simple past tense mastery used in recount text. The researcher used quasi experimental research design. The population of this research is the eleventh grade students of SMA Negeri 2 Sigi, and the samples were the students of XI IPS 2 and XI IPS 4 with the total number of students is 53. The researcher applied purposive random sampling technique. The data were collected through the complement test that consisted of pre-test and post-test. The data were analyzed statistically in order to find out the significant difference of the students’ achievement before and after treatments. The mean score of the pretest of experimental group is 33.78, while the control group is 32.04. The mean score of the posttest of experimental group 74.74, and the control group is 42.27. After analyzing the data t-counted (15.98) is greater than t-table (1.676) by applying 0.05 level of significance and 51 degree of freedom (df). Based on the result of research, it means that the hypothesis is accepted. In conclusion, using English songs can improve students’ simple past tense mastery used in recount text of the eleventh grade at SMA Negeri 2 Sigi